Pengaruh Suku Bunga, Inflasi, dan Nilai Tukar Rupiah terhadap IHSG dengan Profitabilitas sebagai variabel Moderasi - khair, Miftahul; Yeni, Fitri; Wijaya, Ronni Andri (Jurnal Manajemen dan Keuangan, 2024)
In financial market dynamics, a deep understanding of economic factors that affect JCI performance such as interest rates, inflation, and the rupiah exchange rate is essential in making investment decisions. This study aims to analyze the effect of interest rates, inflation, and the rupiah exchange rate on JCI with profitability as moderation. Through a quantitative approach with purposive sampling techniques in 21 LQ45 companies, data were analyzed using SPSS 26. The results showed that interest rates had a negative and significant impact on JCI, while inflation and the rupiah exchange rate had a significant positive impact. Profitability managed to moderate the relationship between interest rates and inflation with JCI significantly. However, profitability did not have a significant impact in moderating the relationship between the rupiah exchange rate and JCI. Researchers highlighted that the combination of low interest rates, controlled inflation, and stable exchange rates boosted JCI growth and the economy as a whole.